Historia splątana Przypadek Historii literatury polskiej Feliksa Bentkowskiego - Markowska, Helena (Śląskie Studia Polonistyczne, 2018)
The article presents discussions on the shape of Polish literary studies which were conducted in connection with the creation of the Historia literatury polskiej [History of Polish Literature] by Feliks Bentkowski. Both the circumstances of the creation of Bentkowski’s work and its reception are presented, with special attention paid to their institutional context, professionalization of philology and bibliography as sciences, as well as to relations between the polemicists. The main part of the article is the reconstruction of the semantics of the historical term “literature”, which is the subject of Bentkowski’s, Jan Śniadecki’s and Gotfryd Ernest Groddeck’s statements. The author advances a thesis that the attempts to define the term “literature” in their texts correspond, in fact, with voices in the debate on the concept of a scientific character of literary studies, which at that time constituted itself as a separate discipline.